Enhancing reading scores with home-to-school connections - Kelley, Michelle (My University, 2013)
The purpose of this study was to increase literacy scores through improving home to school connections. This was done by sending home literacy bags, which included language experience journals, reading calendars, "I Can Read" books, and popcorn words. Knowledge of sight words in the fall semester was compared to knowledge of sight words in the spring semester to determine the effectiveness of the literacy bags. Results of this study showed an increase in sight word knowledge, letter recognition, blending, and rhyming. In conclusion, literacy bags are an effective way to increase reading scores through home to school connections. The author of this study recommends improving the home to school connection through the use of literacy bags and parent communication.
Plan B Paper. 2013. Master of Science in Education- Reading--University of Wisconsin-River Falls. Teacher Education Department. 46 leaves. Includes bibliographical references (leaves 24-25).
Keywords: Reading (Elementary); Reading--Parent participation